Implementasi Kurikulum Berbasis KKNI Menuju Era Revolusi Industri 4.0: Telaah Literatur - Sri Astuti; Zuhrotun Zuhrotun; Kunti Sunaryo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2020)
Curriculum changes in tertiary institutions are routine activities that must be carried out in response to the development of Science and Technology, community needs, and the needs of graduate users. The curriculum currently used is the Indonesian National Qualification Framework or commonly abbreviated as KKNI. Namely the framework for qualifying work qualifications that juxtaposes, equalizes, integrates, the education and training sector as well as work experience in the context of providing work competency recognition in accordance with work positions in various sectors. The rapid development of information technology has influenced all aspects of life, including the business and accounting world. To that end, the curriculum of the accounting study program must harmonize with the development of the information technology. Namely the curriculum in accordance with the development of the Industrial Revolution 4.0. Various attempts have been made by several accounting study programs, including conducting workshops to review existing curricula, integrating the latest information technology materials into several (all) accounting courses currently available, training lecturers related to the latest information technology materials and adding eyes new lectures related to the latest information technology.